The effect of promotion, quality of service and security on customer retention mediated by customer satisfaction on OVO application - Samosir, Vicktor Samuel; Rachbini, Didik J.; Rekarti, Endi (Technium Social Sciences Journal, 2021)
The purpose of this study is to find out and analyze how and how much the significance of promotion, service quality, security to customer satisfaction has implications for customer retention. This research was conducted with a census of 100 respondents. The objective of this research is to empirically prove the variables of promotion, service quality, security, on customer satisfaction in choosing the OVO application, and then have implications for customer retention. This study will also analyze the effect of promotion, service quality, security on customer retention. The results showed that the variable conditions of promotion, service quality, security, had an impact on customer satisfaction in the good category, as well as the effect of promotion, service quality,